Carotenoid metabolic profiling and transcriptome‐genome mining reveal functional equivalence among blue‐pigmented copepods and appendicularia. Issue 11 (June 2014) - Mojib, Nazia; Amad, Maan; Thimma, Manjula; Aldanondo, Naroa; Kumaran, Mande; Irigoien, Xabier
Abstract The tropical oligotrophic oceanic areas are characterized by high water transparency and annual solar radiation. Under these conditions, a large number of phylogenetically diverse mesozooplankton species living in the surface waters (neuston) are found to be blue pigmented. In the present study, we focused on understanding the metabolic and genetic basis of the observed blue phenotype functional equivalence between the blue‐pigmented organisms from the phylum Arthropoda, subclass Copepoda (Acartia fossae) and the phylum Chordata, class Appendicularia (Oikopleura dioica) in the Red Sea. Previous studies have shown that carotenoid–protein complexes are responsible for blue coloration in crustaceans. Therefore, we performed carotenoid metabolic profiling using both targeted and nontargeted (high‐resolution mass spectrometry) approaches in four different blue‐pigmented genera of copepods and one blue‐pigmented species of appendicularia. Astaxanthin was found to be the principal carotenoid in all the species. The pathway analysis showed that all the species can synthesize astaxanthin from β‐carotene, ingested from dietary sources, via 3‐hydroxyechinenone, canthaxanthin, zeaxanthin, adonirubin or adonixanthin. Further, using de novo assembled transcriptome of blue A. fossae (subclass Copepoda), we identified highly expressed homologous β‐carotene hydroxylase enzymes and putative carotenoid‐binding proteins responsible for astaxanthin formation and the blue phenotype. In blue O. dioica (class Appendicularia), corresponding putative genes were identified from the reference genome. Collectively, our data provide molecular evidences for the bioconversion and accumulation of blue astaxanthin–protein complexes underpinning the observed ecological functional equivalence and adaptive convergence among neustonic mesozooplankton.